Study on Filling Material Ratio and Filling Effect: Taking Coarse Fly Ash and Coal Gangue as the Main Filling Component. (2nd June 2019) - Wang, Changxiang; Liu, Yin; Hu, Hao; Li, Yangyang; Lu, Yao
Abstract : Filling mining is an effective way to settle the dilemma of "Three Down and One Above" in coal mining. Fly ash and coal gangue can be used as filling materials with significant social, economic, and environmental benefits. Using coarse fly ash base as cementing material and coal gangue as aggregate, orthogonal experiment of filling paste was conducted in this study. The range analysis was performed for the strength and transportation requirements of filling paste, and the optimum proportion was determined by the comprehensive balance method. In order to verify the filling effect, a dynamic filling simulation device was designed, and a comparative simulation test of caving mining and dynamic filling mining was carried out. Results show that the filling paste with fly ash and coal gangue as the main component can meet the requirements of filling design and application. This research provides a reference for the material selection and proportion design of paste filling.